Activation of inflammatory/coagulation system following electrical cardioversion of patient with recent onset atrial fibrillation: an explorative study of the relation to white matter hyperintensities. (25th November 2020) - Arvanitis, P; Johansson, A.K; Frick, M; Malmborg, H; Larsson, E.M; Blomstrom Lundqvist, C
Abstract: Background: White matter hyperintensities (WMH), assessed using Fazekas scale, are more prevalent in patients with atrial fibrillation (AF), although its pathophysiologic mechanism(s) is unclear. Purpose: The study objective was to explore the association between cardiac, inflammatory and coagulation biomarkers and white matter hyperintensities in anticoagulant-naïve patients following electrical cardioversion (CV) of recent onset AF. Methods: Patients with AF duration <48 hours were prospectively included. Brain magnetic resonance imaging (MRI), C-reactive protein (CRP), high-sensitivity troponin T (hs-TNT), NT-proBNP, Interleukin 6, P-selectin, D-dimer, prothrombin fragment 1+2, von Willebrand factor Ag, coagulation factor VIII C and fibrinogen, were obtained sequentially prior, after (2–4 hours) and 7–10 days following CV. Repeated measure analysis of variance was performed. Results: Forty-three patients (84% males), aged 55±9.6 years, (mean±SD) with median CHA2DS2-VASc score 1 (interquartile range 0–1) were included. Sequential MRI showed no new brain lesions after CV, while WMH were present at baseline in 21/43 (49%) patients. Repeated measure analysis of variance revealed a statistically significant overall change for hs-TNT: F(2, 84)=6.056, p=0.03, NT-proBNP: F(2, 84)=106.02, p<0.001, P-selectin: F(2, 84)=8.69, p<0.001 and vWF:Ag: F(2, 84)=4.078, p=0.02. CRP, IL-6, coagulation factor VIII-C and fibrinogen showed the same pattern, however none reached statistical significance. Patients with WMH had persistent higher values for CRP, hs-TNT, D-dimer, prothrombin fragment 1+2 and fibrinogen prior and after CV, as values at 7–10 days coincided; however, statistical interaction was not significant. Conclusion: Transient activation of inflammatory and coagulation systems during atrial fibrillation subsides within 7–10 days after electric cardioversion of recent onset atrial fibrillation. A tendency of higher degree of activation during atrial fibrillation was observed in patients with white matter hyperintensities. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swedish Heart-Lung Foundation, Swedish Research Council, Correvio International Sárl (Geneva Switzerland), Selanders Stiftelse